Victims' rights: serving victims or the criminal justice system? An empirical study on victims of violent crime and their experiences with the Danish police. Issue 1 (2nd January 2021) - Holmberg, Lars; Johansen, Louise Victoria; Asmussen, Ida Helene; Birkmose, Sofie Meldal; Adrian, Lin
ABSTRACT: This paper describes how victims of violence experience their initial meeting with the Danish police and the time that follows. Based on observations of police-victim encounters and interviews with victims, we explore how victims' rights are brought into play when victims report crimes to the police. Such rights are meant to help victims cope with their situation. However, our study shows that rights are not always adhered to and are at times administered in ways that suit the needs of the criminal justice system more than those of victims. Our study also shows that rights do not always reflect the needs of victims. We point to the incremental development and piecemeal nature of victims' rights in Denmark as a possible explanation for the current state of affairs.